Harmonisation and standardisation of health sector and programme reviews and evaluations – how can they better inform health policy dialogue?. Issue 1 (December 2016) - Nabyonga-Orem, Juliet; Tumusiime, Prosper; Nyoni, Jennifer; Kwamie, Aku
Abstract Background Health sector and programme performance assessments provide a rich source of contextual data directly linked to implementation of programmes and can inform health policy dialogue, planning and resource allocation. In seeking to maximise this opportunity, there are challenges to overcome. A meeting convened by the World Health Organization African Region discussed the strengths, weaknesses and challenges to harmonising and standardising health sector and programme performance assessments, as well as use of evidence from such processes in decision making. This article synthesises the deliberations which emerged from the meeting. Discussing these in light of other literature we propose practical options to standardising health sector and programme performance assessment and improve realisation of using evidence in decision making. Discussion Use of evidence generated from health sector and programme performance assessments into regular country processes of sectoral monitoring, dialogue and policy modification is crucial. However, this process faces several challenges. Identified challenges were categorised under several themes, namely the weak institutional capacities for monitoring and evaluation in reference to weak health information systems, a lack of tools and skills, and weak accountability mechanisms; desynchronised planning timeframes between programme and overall health sector strategies; inadequate time to undertake comprehensive and good quality performance assessment; weak mechanisms for following up on implementation of recommendations; lack of effective stakeholder participation; and divergent political aspirations. Conclusion The question of what performance assessment is for in a country must be asked and answered clearly if the utility of these processes is to be realised. Standardising programme and sector reviews offers numerable opportunities that need to be maximised. Identified challenges need to be overcome through strengthened Ministry of Health leadership, effective stakeholder engagement and institutionalising follow-up mechanisms for agreed recommendations. In addition, health sector performance assessments need to be institutionalised as part of the accountability mechanism, and they must be planned for and funding secured within annual budget and medium term expenditure frameworks.